Vitamin D deficiency and tension-type headaches in children - literature review - Zieliński, Grzegorz; Ginszt, Michał; Filipiak, Zuzanna; Suwała, Marta; Majcher, Piotr (Journal of Education, Health and Sport, 2019)
IntroductionTension-type headache (TTH) is perceived as bilateral pressure, tension or non-pulsatile mild to moderate headache. The etiopathogenesis of the occurrence of this phenomenon among children has been extrapolated from adult studies. The purpose of this review was to show the association between tension-type headaches and vitamin D deficiency in children based on available literature.Materials and methodsSystematic review based on the content of PubMed, ResearchGate, and Google Scholar databases was performed. In order to identify relevant publications, a search was performed using a combination of key words: "children", "tension-type headache", "vitamin D", "25 (OH) D". Three studies have been included in our review.ResultsConsidering the value of the evidence and the results in peer-reviewed publications, we conclude that there is too little evidence to support the hypothesis that there is a connection between tension-type pains and vitamin D deficiency in children.ConclusionsDue to the small amount of available literature, research on the effects of vitamin D deficiency on tension-type headaches in children should be continued on a larger scale. Based on the above analysis, we find that there is too little evidence to support the hypothesis that the level of vitamin D affects the development of tension-type headaches in children.